2016
DOI: 10.5301/jva.5000526
|View full text |Cite
|
Sign up to set email alerts
|

Graft Modification Strategies to Improve Patency of Prosthetic Arteriovenous Grafts for Hemodialysis

Abstract: Prosthetic arteriovenous grafts (AVGs) are indicated for vascular access for long-term hemodialysis in patients in whom creation or maintenance of an arteriovenous fistula (AVF) has failed or is contraindicated. AVGs have an inferior long-term patency as compared to AVFs. To ameliorate patency rates of prosthetic AVGs, different strategies have emerged to improve graft materials. This review aims to describe current strategies and future perspectives on graft modification, by graft geometry, drug coatings and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…Hemodynamically optimized graft designs have been proposed to increase AVG longevity by reducing hemodynamic disturbances near the graft-vein anastomosis [ 3 ]. The hemodynamic benefit of these grafts is typically assessed and demonstrated using computational fluid dynamics (CFD) simulations [ 4 11 ], because, as opposed to experimental in vitro techniques, CFD modelling allows for straightforward, high resolution assessment of WSS parameters and for simultaneous evaluation of multiple graft designs.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodynamically optimized graft designs have been proposed to increase AVG longevity by reducing hemodynamic disturbances near the graft-vein anastomosis [ 3 ]. The hemodynamic benefit of these grafts is typically assessed and demonstrated using computational fluid dynamics (CFD) simulations [ 4 11 ], because, as opposed to experimental in vitro techniques, CFD modelling allows for straightforward, high resolution assessment of WSS parameters and for simultaneous evaluation of multiple graft designs.…”
Section: Introductionmentioning
confidence: 99%
“…NIH development is believed to be triggered by disturbed blood flow and non‐physiological wall shear stresses (WSS) around the venous anastomosis 1,2 . Although the exact haemodynamic trigger for NIH development is unknown, 3 various novel graft designs have been proposed to reduce disturbed flow and non‐physiological WSS at the graft‐vein anastomosis 4 …”
Section: Introductionmentioning
confidence: 99%
“…Most research on minimising disturbed flow and normalising WSS patterns at the graft-vein anastomosis has focused on modifying graft geometry. 4 Strikingly, the impact of haemodialysis (HD) needle flow on AVG haemodynamics is often neglected, even though it has been shown that needle flow can result in increased flow disturbance. 5e7 Most HD patients receive dialysis according to intermittent or daily dialysis programs that amount to 12e36 h per week.…”
Section: Introductionmentioning
confidence: 99%